From Wrinkles to Wisdom: A Comparative Study of the Social Representations of Ageing among Brazilian and Spanish People - Igor Eduardo de Lima Bezerra; Ludgleydson Fernandes De Araújo; Evair Mendes da Silva Sousa; Mateus Egilson da Silva Alves; Reina Granados; Pablo Mangas (Research on Ageing and Social Policy)
Population ageing is a growing global phenomenon. It occurs in various realities, is multifactorial, heterogeneous and dynamic. Perceptions on the subject are also diverse. This study is based on Moscovici's theory of Social Representations, which seeks to explain how phenomena can be understood through socially shared ideas. The aim was to comparatively identify the conceptions of Brazilians and Spaniards about ageing. 500 people took part: 250 Brazilians and 250 Spaniards. The study is qualitative, comparative, descriptive, with cross-sectional data and a non-probabilistic sample. To collect the data, a sociodemographic questionnaire was administered and a guiding question was asked: “What does ageing mean to you?”. Analyses were carried out using SPSS Statistics and Iramuteq software, respectively. Among the representations obtained, the similarities were: a natural process, with bodily changes and that health is necessary to enjoy the last phase of life. Among the differences, there was ambiguity among Brazilians, who understood the phenomenon as something bad, but endowed with knowledge and wisdom. The Spanish were more specific about maturing, citing deterioration, wrinkles and illnesses. It is hoped that this study will encourage others to demystify ideas on the subject and support actions for good ageing in different contexts.